Impact of Training and Development on Employees Performance atHotel in, Greater Noida (Global Journal of Management and Business Research, 2022)
The hotel industry faces many challenges in developing a food and beverage training department for people's Inhofe. The objective of this study is to distinguish between undergraduate training and theoretical research into the training and development of the crown plaza.The most effective and motivating teaching and learning takes place in an organization where knowledge and training are updated by directing global affairs.
Keywords: training and development; training on the job; training analysis; job satisfaction